2019
DOI: 10.1200/jco.2019.37.4_suppl.288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity upon the survival of cholangiocarcinoma patients.

Abstract: 288 Background: Obesity is a risk factor for developing cholangiocarcinoma (CCA). However, the effect of obesity on survival of CCA is unclear. The primary aim of this study was to analyze the impact of obesity upon overall survival of CCA patients. Secondary aims were to analyze impact of obesity upon other disease characteristics such as tumor site, stage, age, sex, BMI and Ca 19-9. Methods: A total of 411 unique pts diagnosed with CCA at Mayo Clinic Florida between 2000 and 2018 were retrieved from our col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There are controversial data regarding the impact of metabolic risk factors and outcomes in patients with CCA. In a database from Mayo Clinic Florida, BMI did not make a significant impact on the survival, and there was no difference in the overall survival for obese compared to normal or overweight patients with CCA [ 32 ]. Nevertheless, a multicenter study suggested that NASH was related to higher mortality rate in patients with CCA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are controversial data regarding the impact of metabolic risk factors and outcomes in patients with CCA. In a database from Mayo Clinic Florida, BMI did not make a significant impact on the survival, and there was no difference in the overall survival for obese compared to normal or overweight patients with CCA [ 32 ]. Nevertheless, a multicenter study suggested that NASH was related to higher mortality rate in patients with CCA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%